Estimation of absorbed radiation dose rates in wild rodents inhabiting a site severely contaminated by the Fukushima Dai-ichi nuclear power plant accident. (April 2015) - Kubota, Yoshihisa; Takahashi, Hiroyuki; Watanabe, Yoshito; Fuma, Shoichi; Kawaguchi, Isao; Aoki, Masanari; Kubota, Masahide; Furuhata, Yoshiaki; Shigemura, Yusaku; Yamada, Fumio; Ishikawa, Takahiro; Obara, Satoshi; et al.
Abstract: The dose rates of radiation absorbed by wild rodents inhabiting a site severely contaminated by the Fukushima Dai-ichi Nuclear Power Plant accident were estimated. The large Japanese field mouse ( Apodemus speciosus ), also called the wood mouse, was the major rodent species captured in the sampling area, although other species of rodents, such as small field mice ( Apodemus argenteus ) and Japanese grass voles ( Microtus montebelli ), were also collected. The external exposure of rodents calculated from the activity concentrations of radiocesium ( 134 Cs and 137 Cs) in litter and soil samples using the ERICA (Environmental Risk from Ionizing Contaminants: Assessment and Management) tool under the assumption that radionuclides existed as the infinite plane isotropic source was almost the same as those measured directly with glass dosimeters embedded in rodent abdomens. Our findings suggest that the ERICA tool is useful for estimating external dose rates to small animals inhabiting forest floors; however, the estimated dose rates showed large standard deviations. This could be an indication of the inhomogeneous distribution of radionuclides in the sampled litter and soil. There was a 50-fold difference between minimum and maximum whole-body activity concentrations measured in rodents at the time of capture. The radionuclides retained in rodents after capture decreased exponentially over time. Regression equations indicated that the biological half-life of radiocesium after capture was 3.31 d. At the time of capture, the lowest activity concentration was measured in the lung and was approximately half of the highest concentration measured in the mixture of muscle and bone. The average internal absorbed dose rate was markedly smaller than the average external dose rate (<10% of the total absorbed dose rate). The average total absorbed dose rate to wild rodents inhabiting the sampling area was estimated to be approximately 52 μGy h −1 (1.2 mGy d −1 ), even 3 years after the accident. This dose rate exceeds 0.1–1 mGy d −1 derived consideration reference level for Reference rat proposed by the International Commission on Radiological Protection (ICRP). Highlights: Wild rodents and environmental media were collected in a Fukushima evacuation area. The external absorbed dose rates calculated using the ERICA tool were almost the same as those measured with glass dosimeters. The average internal absorbed dose rate was markedly smaller than the average external dose rate. The biological half-life of radiocesium after wild rodent capture was 3.31 d. The estimated average total absorbed dose rate was approximately 52 μGy h −1 (1.2 mGy d −1 ).